Estimation of the Latitude, the Gnomon’s Length and Position About Sinbeop-Jipyeong-Ilgu in the Late of Joseon Dynasty - Byeong-Hee Mihn; Yong Sam Lee; Sang Hyuk Kim; Won-Ho Choi; Seon Young Ham (Journal of Astronomy and Space Sciences, 2017)
In this study, the characteristics of a horizontal sundial from the Joseon Dynasty were investigated. Korea’s Treasure No. 840 (T840) is a Western-style horizontal sundial where hour-lines and solar-term-lines are engraved. The inscription of this sundial indicates that the latitude (altitude of the north celestial pole) is 37° 39´, but the gnomon is lost. In the present study, the latitude of the sundial and the length of the gnomon were estimated based only on the hour-lines and solar-termlines of the horizontal sundial. When statistically calculated from the convergent point obtained by extending the hourlines, the latitude of this sundial was 37° 15´ ± 26´, which showed a 24´ difference from the record of the inscription. When it was also assumed that a convergent point is changeable, the estimation of the sundial’s latitude was found to be sensitive to the variation of this point. This study found that T840 used a vertical gnomon, that is, perpendicular to the horizontal plane, rather than an inclined triangular gnomon, and a horn-shaped mark like a vertical gnomon is cut on its surface. The length of the gnomon engraved on the artifact was 43.1 mm, and in the present study was statistically calculated as 43.7 ± 0.7 mm. In addition, the position of the gnomon according to the original inscription and our calculation showed an error of 0.3 mm.